Development of a prognostic index for 90-day mortality in patients discharged after admission to hospital for community-acquired pneumonia. Issue 6 (22nd February 2009) - Capelastegui, A; España, P P; Quintana, J M; Bilbao, A; Menendez, R; Zalacain, R; Torres, A
Abstract : Background: Although patients admitted to hospital for community-acquired pneumonia (CAP) experience substantial short-term mortality following hospital discharge, few studies have focused on identifying factors that predict mortality after admission to hospital in this population. The objective of this study was to develop and validate a prognostic index for 90-day mortality after hospital discharge among patients with CAP. Methods: The prognostic index was derived in 1117 adult patients discharged between 2003 and 2007 from a general hospital following admission for CAP. It was validated in 646 consecutive patients with CAP discharged from three other hospitals between 1 November 2005 and 31 July 2006. Risk factors evaluated included host-related factors, severity upon admission, in-hospital management and bacteriology. Results: In the derivation cohort, three factors were independently associated with 90-day mortality: pre-illness functional status, Charlson index (composite measure of co-morbid illnesses) and severity on admission. Mortality at 90 days was 0.7% in the low-risk group, 3.5% in the intermediate-risk group and 17.2% in the high-risk group. In the validation cohort, 90-day mortality in the three groups was 0.6%, 3.9% and 19.6%, respectively. Compared with the low-risk group, the odds ratio for mortality was 43.5 for the high-risk group. The risk categories showed an area under the receiver operating characteristic curve of 0.79 in the derivation cohort and 0.82 in the validation cohort. Conclusions: The prognostic index accurately stratifies patients admitted to hospital for CAP into low-, intermediate- and high-risk groups for 90-day mortality on discharge. The use of this index could help clinicians improve outcomes in this vulnerable population by targeting specific interventions to each group.